(untitled) - Foster, Graham (Hoboken, N.J., 2007)
In The Power of Positive Profit, business expert Graham Foster attacks the issue of false business success promoted through volume selling, cost cutting, or both, and offers powerful business lessons and breakthroughs for making an appropriate profit while maintaining or even sharpening your competitive edge.
Keywords: Corporate profits,Sales management,Cost control